Prospects for finding Junge variability-lifetime relationships for micropollutants in the Danube river. Issue 9 (7th August 2019) - Coll, Claudia; Lindim, Claudia; Sobek, Anna; Sohn, Michael D.; MacLeod, Matthew
Abstract : Junge variability-lifetime relationships could potentially be used to infer persistence of micropollutants in rivers from field measurements of concentrations. Abstract : Persistence of chemical pollutants is difficult to measure in the field. Junge variability-lifetime relationships, correlating the relative standard deviation of measured concentrations with residence time, have been used to estimate persistence of air pollutants. Junge relationships for micropollutants in rivers could provide evidence that half-lives of compounds estimated from laboratory and field data are representative of half-lives in a specific system, location and time. Here, we explore the hypothesis that Junge relationships could exist for micropollutants in the Danube river using: (1) concentrations of six hypothetical chemicals modeled using the STREAM-EU fate and transport model, and (2) concentrations of nine micropollutants measured in the third Joint Danube Survey (JDS3) combined with biodegradation half-lives reported in the literature. Using STREAM-EU, we found that spatial and temporal variability in modeled concentrations was inversely correlated with half-life for the four micropollutants with half-lives ≤90 days. For these four modeled micropollutants, we found Junge relationships with slopes significantly different from zero in the temporal variability of concentrations at 88% of the 67 JDS3 measurement sites, and in the spatial variability of concentrations on 36% out of 365 modeled days. A Junge relationship significant at the 95% confidence level was not found in the spatial variability of nine micropollutants measured in the JDS3, nor in STREAM-EU-modeled concentrations extracted for the dates and locations of the JDS3. Nevertheless, our model scenarios suggest that Junge relationships might be found in future measurements of spatial and temporal variability of micropollutants, especially in temporal variability of pollutants measured downstream in the Danube river.